PERANAN MOTIVASI KERJA GUNA MENINGKATKAN PRODUKTIVITAS PEGAWAI PADA SATUAN POLISI PAMONG PRAJA (SATPOL PP) KABUPATEN MANOKWARI - Hamidah, Kusnul; Budiman, Budiman; Balia, Nikolina (POLITEKNIK LP3I JAKARTA, 2026)
Work motivation plays a strategic role in shaping employee productivity, particularly in government agencies tasked with enforcing regional regulations such as the Civil Service Police Unit (Satpol PP). This study aims to analyze the influence of work motivation on the productivity of Satpol PP employees in Manokwari Regency. A descriptive quantitative approach was employed by distributing questionnaires to 40 respondents, including both structural officials and operational staff. Data were analyzed using validity, reliability, frequency distribution, and simple linear regression tests. The results reveal a positive and significant effect of work motivation on employee productivity, with a determination coefficient of 55.1%. Self-actualization and responsibility emerged as the most influential factors, while self-esteem remained an area for improvement. Overall, employees demonstrated high motivation and strong commitment to their duties, though continuous supervision and recognition systems are needed to sustain motivation levels. These findings underscore the importance of motivation-based human resource management policies to enhance the performance and productivity of public service officers in regional governance.